On asymptotic formulas for solutions of systems of linear differential equations with a degerate matrix with derivatives - Samusenko, P. F.; ShkiI, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
In this paper, we suggest a method for the construction of asymptotic formulas for solutions of systems of differential equations in the case where the roots of the characteristic equation are simple